Rooftop PV System Optimization in an Educational Building Using SAM: A Case Study at UPN Veteran Jawa Timur - Yofinda Eka Setiawan; Allif Rosyidy Hilmi (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
The implementation of sustanable energy in educational institutions recognizes the potential of rooftop photovoltaic (PV) systems as a viable energy source. This research aims to evaluate and optimize the design of a rooftop photovoltaic (PV) system for Building 1 of the Fakultas Teknik dan Sains (FTS) at Universitas Pembangunan Nasional "Veteran" Jawa Timur (UPNVJT) using the System Advisor Model (SAM) software. Integrated data including meteorological data, building characteristics, and solar panel system specifications were utilized. The available rooftop area for PV system installation is approximately 200 m² with a north-facing orientation, which is estimated to accommodate a 30 kWp PV system capacity. Tilt angle and azimuth scenarios were varied to achieve maximum energy production. Based on SAM simulations, the optimal installation angle of 15° tilt and azimuth generated an annual energy output of 44,052 kWh with a performance ratio of 71% and a capacity factor of 17%. This study confirms that rooftop PV installation at FTS UPNVJT is technically feasible, and it is expected to serve as a foundation for the gradual implementation of PV systems as part of green campus initiatives and energy transition in educational institutions.